2018
DOI: 10.3389/fcvm.2018.00188
|View full text |Cite
|
Sign up to set email alerts
|

Vasculoprotective Role of Olive Oil Compounds via Modulation of Oxidative Stress in Atherosclerosis

Abstract: Existing evidence supports the significant role of oxidative stress in the endothelial injury, and there is a direct link between increased oxidative stress, and the development of endothelial dysfunction. Endothelial dysfunction precedes the development of atherosclerosis and subsequent cardiovascular disease (CVD). The overproduction of reactive oxygen species facilitates the processes, such as oxidative modification of low-density lipoproteins and phospholipids, reduction in the NOS-derived nitric oxide, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 113 publications
2
31
0
4
Order By: Relevance
“…In this study, significant differences were observed with respect to inflammatory markers in the aorta tissues among groups treated with HFD and HFD + CEVOO, CaOO or ClOO. Indeed, in HDF fed rats, expression of COX-2, mPGES1, and iNOS was higher than in the standard diet fed rats, and the HFD + CEVOO, CaOO or ClOO groups showed a remarkable decrease of the inflammatory status of rat aorta, while increasing protective vascular markers, in line with other findings [69,70]. No significant alterations were observed for enzymes involved in the control of redox state.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, significant differences were observed with respect to inflammatory markers in the aorta tissues among groups treated with HFD and HFD + CEVOO, CaOO or ClOO. Indeed, in HDF fed rats, expression of COX-2, mPGES1, and iNOS was higher than in the standard diet fed rats, and the HFD + CEVOO, CaOO or ClOO groups showed a remarkable decrease of the inflammatory status of rat aorta, while increasing protective vascular markers, in line with other findings [69,70]. No significant alterations were observed for enzymes involved in the control of redox state.…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review and meta-analysis [186] reported that a regular consumption of EVOO (approximately between 1 and 50 mg daily) could favorably affect circulating inflammatory biomarkers, known as acute-phase reactants, and the flow-mediated vasodilation, thus contributing to the CVD protective effects of the MedDiet, observed in epidemiological studies [37,38]. Major phenolic compounds within EVOO, such as hydroxytyrosol and oleuropein, can directly target and inhibit the expression of cytokines, chemokines and adhesion molecules, induced by inflammatory stimuli, in human endothelial in vitro systems, via blocking the signaling of nuclear factor-kB (NF-kB), which is a critical regulator of the inflammatory response [187]. However, in a synergistic cooperation with endothelial cells, smooth muscle cells (SMCs) perform also essential functions in sustaining vascular homeostasis, so that their reciprocal interactions may represent novel therapeutic targets for anti-atherogenic interventions [188].…”
Section: Influence Of Polyphenols On Endothelial Dysfunction and Athementioning
confidence: 99%
“…The beneficial effects of the Mediterranean diet have been attributed to the consumption of olive oil as well as of vegetables, fruits, nuts, legumes, unprocessed cereals, and fish. Several studies have shown the cardioprotective, antithrombotic and antiinflammatory properties of olive oil [9][10][11]. There are two types of olive oil depending on the production mechanisms, extra virgin olive oil (EVOO) and refined olive oil (ROO).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial properties of olive oil, including the cardioprotective ones, have been long attributed to its high MUFAs content. However, several studies have also highlighted the antioxidant beneficial effects of the minor components (mainly phenolic compounds) of EVOO regarding reducing thrombotic risk, inflammation, atherosclerosis, oxidative stress and cancer [11][12][13]. Most previous studies made no distinction among the different varieties of olive oil (EVOO or ROO) when investigating the effects of olive oil consumption on health, despite the different contents of minor bioactive components.…”
Section: Introductionmentioning
confidence: 99%